Cartel overcharges and the deterrent effect of EU competition law - Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper examines cartel overcharges for the European market. Using a sample of 191 overcharge estimates and several parametric and semi-parametric estimation procedures, the impact of different cartel characteristics and the market environment on the magnitude of overcharges is analyzed. The mean and median overcharge rates are found to be 20.70 percent and 18.37 percent of the selling price and the average cartel duration is 8.35 years. Certain cartel characteristics and the geographic region of cartel operation influence the level of overcharges considerably. Furthermore, empirical evidence suggests that the currently existing fine level of the EU Guidelines is too low to achieve optimal deterrence.
urn:nbn:de:bsz:180-madoc-324973
Keywords: L13; L41; L44; 330; cartels; overcharges; Europe; fines; deterrence; damages; Kartell; Betriebliche Preispolitik; Wettbewerbsaufsicht; Strafe; EU-Wirtschaftsrecht; EU-Staaten